Prophetic Journalism of Islamic Media: Nursyam Centre in Promoting Moderation: Jurnalistik Profetik Media Islam: Nur Syam Centre dalam Menggelorakan Moderasi Beragama - Nurhalizah, Mevy (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to the role of prophetic journalism in Islamic media with a focus on the Nursyam Centre (NSC) as one of the important actors in voicing religious moderation in Indonesia. Using a descriptive qualitative approach, this study examines how prophetic journalistic principles based on prophetic values such as humanization, liberation, and transcendence are implemented in the narratives and content produced by the NSC. Data collection was carried out through in-depth interviews with NSC contributors, as well as document analysis of digital content published on www.nursyamcentre.com website. The data analysis technique used refers to the principles of prophetic journalism as developed by Kuntowijoyo, namely humanization (amar ma'ruf), liberation (nahi munkar) and transcendence (monotheism). The results of the study show that the NSC actively produces Islamic content that promotes interfaith dialogue, tolerance, and rejection of extremism. NSC also positions itself as an alternative public space that integrates journalism with cultural da'wah values based on local wisdom. This study concludes that prophetic journalism applied by the NSC is not only a means of disseminating information, but also an instrument of social transformation and public education in building a moderate, inclusive, and contextual understanding of Islam. The Nursyam Center is an example of how religious media, without sacrificing journalistic quality, can become a place for da'wah that is educational, liberating, and spiritual. Their content gave birth to Islamic media rahmatan lil'alamin in the digital era.